Migrant Age Profiles and Long‐Run Living Standards in Australia. (22nd November 2019) - Parr, Nick; Guest, Ross
Abstract: The age profile of immigration to Australia can be altered by public policies. This article applies a method of valuing long term population paths in order to evaluate alternative immigrant age profiles based on a proxy indicator of living standards over time for Australia. Results show that the variation in value of the population path follows an inverted U‐shape by immigrant's age. The strength of preference between immigrants aged 20–29 years and older working age immigrants reduces as the social discount rate increases. Higher life expectancy and lower fertility accentuate preference for younger working age immigrants.